The excessive Mortality of British Residents in India, as affecting the choice of the Civil Service of the East India Company as a career for young men - Hancock, W. Neilson (Dublin Statistical Society, 1855)
In this paper I propose to direct your attention to some facts, commonly overlooked, but which ought, nevertheless, to be fully considered by those who have to decide either for themselves or for others, as to the wisdom of choosing an Indian career. A young man commencing life would naturally desire an employment in which he had a reasonable prospect of attaining the usual period of human life, that he might first qualify himself for performing some duties serviceable to mankind ; then spend his manhood in discharging them; and in old age retire to a dignified position of influence, which a well-spent life is calculated to produce. Now what prospect of prolonged life has the successful competitor of the Indian examination ? To solve this question, I have no elaborate statistics to produce; but the calculations for commercial speculations, though only rough approximations, are free from any risk of gross error or willful exaggeration.
Read 16th April, 1855
Keywords: Colonists, Mortality; India; Colonial careers; 314.15